Public Health Services Through the Active Participation Movement to Eliminate Stunting Towards a Healthy Indonesia - Wiradi Suryanegara; Vidi Posdo A. Simarmata; Dio Ardhito Indrawan; Angela Lady Kezia; Andi Jesilia Rahmadantia (International Journal Of Community Service, 2025)
Addressing stunting in Indonesia has of course become a government priority, but if it's just the government itself, it's certainly not enough. An active and participatory role from all stakeholders is a necessity in overcoming stunting, because it is not enough just to involve policies, direct intervention actions in the community to raise awareness and increase awareness must also be carried out. Preventive measures to prevent additional stunting from occurring both quantitatively and qualitatively, and curative measures to assist communities who are suspected of having the potential or even indications of stunting to minimize the resulting risks. For this reason, UKI is present through community service activities at the UKI Faculty of Medicine in the Active Participation movement to Eliminate Stunting Towards a Healthy Indonesia called PkM PARIPURNA. The focus locations (loci) for the activity targets are seven villages in Rancakalong District, Sumedang Regency, West Java with core activities centered at the Rancakalong District Health Center including General Post, IGD Post, KIA Post, and Farmas Post with types of activities in the form of examination services, treatment, education and training. Activities will be carried out from May to August 2023 with a team consisting of lecturers and young doctors from the UKI Faculty of Medicine. The PkM activities were carried out well and received an extraordinary response from the community in seven villages in Rancakalong District, Sumedang Regency. From the results of examination service activities, data was obtained that the majority of people suffer from non-communicable diseases such as hypertension, diabetes, gout, and others, while for children it is dominated by fever, cough, and diarrhea. Educational activities regarding balanced nutrition for pregnant women and toddlers were also carried out well, there was an increase in participants' knowledge about various information regarding the prevention and management of stunting. It was concluded that the active participation movement to eliminate stunting towards a healthy Indonesia could be a priority choice because it is very effective and has great benefits for society.